Systematic review of clinician-directed nudges in healthcare contexts. Issue 7 (12th July 2021) - Last, Briana S; Buttenheim, Alison M; Timon, Carter E; Mitra, Nandita; Beidas, Rinad S
Abstract : Objective: Nudges are interventions that alter the way options are presented, enabling individuals to more easily select the best option. Health systems and researchers have tested nudges to shape clinician decision-making with the aim of improving healthcare service delivery. We aimed to systematically study the use and effectiveness of nudges designed to improve clinicians' decisions in healthcare settings. Design: A systematic review was conducted to collect and consolidate results from studies testing nudges and to determine whether nudges directed at improving clinical decisions in healthcare settings across clinician types were effective. We systematically searched seven databases (EBSCO MegaFILE, EconLit, Embase, PsycINFO, PubMed, Scopus and Web of Science) and used a snowball sampling technique to identify peer-reviewed published studies available between 1 January 1984 and 22 April 2020. Eligible studies were critically appraised and narratively synthesised. We categorised nudges according to a taxonomy derived from the Nuffield Council on Bioethics. Included studies were appraised using the Cochrane Risk of Bias Assessment Tool. Results: We screened 3608 studies and 39 studies met our criteria. The majority of the studies (90%) were conducted in the USA and 36% were randomised controlled trials. The most commonly studied nudge intervention (46%) framed information for clinicians, often through peer comparison feedback. Nudges that guided clinical decisions through default options or by enabling choice were also frequently studied (31%). Information framing, default and enabling choice nudges showed promise, whereas the effectiveness of other nudge types was mixed. Given the inclusion of non-experimental designs, only a small portion of studies were at minimal risk of bias (33%) across all Cochrane criteria. Conclusions: Nudges that frame information, change default options or enable choice are frequently studied and show promise in improving clinical decision-making. Future work should examine how nudges compare to non-nudge interventions (eg, policy interventions) in improving healthcare.